2021
DOI: 10.1172/jci130740
|View full text |Cite
|
Sign up to set email alerts
|

Galectin-7 downregulation in lesional keratinocytes contributes to enhanced IL-17A signaling and skin pathology in psoriasis

Abstract: Psoriasis is a chronic inflammatory skin disease characterized by inflammatory cell infiltration, as well as hyperproliferation of keratinocytes in skin lesions, and is considered a metabolic syndrome. We found that the expression of galectin-7 is reduced in the skin lesions of patients with psoriasis. IL-17A and TNFα, two cytokines intimately involved in the development of psoriatic lesions, suppressed galectin-7 expression in human primary keratinocytes (HEKn cells) and the immortalized human keratinocyte ce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
34
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(35 citation statements)
references
References 33 publications
1
34
0
Order By: Relevance
“…Galectin-7 is highly expressed in epithelial tissues, especially stratified squamous epithelium, which corroborates this finding [ 38 ]. Galectin-7 was found to play a role in the pathogenesis of psoriasis, an inflammatory process affecting stratified squamous cells of the skin by elevating levels of IL-6 and IL-8 [ 39 ]. The elevated serum levels of galectin-7 in patients with tumors of squamous cell origin help to explain the origin of galectins in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…Galectin-7 is highly expressed in epithelial tissues, especially stratified squamous epithelium, which corroborates this finding [ 38 ]. Galectin-7 was found to play a role in the pathogenesis of psoriasis, an inflammatory process affecting stratified squamous cells of the skin by elevating levels of IL-6 and IL-8 [ 39 ]. The elevated serum levels of galectin-7 in patients with tumors of squamous cell origin help to explain the origin of galectins in the serum.…”
Section: Discussionmentioning
confidence: 99%
“…Gal-7 production is regulated by p53, TNF-α and NFĸB ( 97 ), but based on upstream promotor region sequencing it is predicted that LGALS7 and LGALS7B may each be regulated by different transcription factors ( 97 , 99 , 107 ). Studies to date suggest that gal-7 has key functions in epithelial cell homeostasis, including cell growth, differentiation and apoptosis as well as functions in cell adhesion, migration and immune cell regulation ( 101 , 108 ; 97 , 105 , 106 , 109 116 ).…”
Section: Galectin-7mentioning
confidence: 99%
“…In vivo administration of exogenous gal-7 to pregnant mice during mid-gestation results in a pro-inflammatory response with elevated placental IL-1 β and IL-6 and reduced IL-10 mRNA production ( 120 ). Other reports however, indicate that gal-7 has anti-inflammatory actions treatment of PMA-stimulated Jurkat cells with gal-7 inhibits IL-2 and INF-γ production ( 112 ), gal-7 silencing elevates IL-17A-stimulated HaCaT cell secretion of IL-6 and IL-18 ( 107 ) and gal-7 is down-regulated in a mouse model of psoriasis ( 107 ). Therefore, the immune regulatory role of gal-7 may be cell-type specific and/or may depend on its cellular localization.…”
Section: Galectin-7mentioning
confidence: 99%
“…More recently, it was found that the expression of galectin-7 is reduced by cytokines in the skin lesions of patients with psoriasis. This results in the hyperproliferation of keratinocytes and skin inflammation [ 20 ].…”
Section: Galectin-7 a Convergence Of Pathology With Physiologymentioning
confidence: 99%